2021
DOI: 10.3389/fcvm.2021.610915
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Radiation Therapy May Be Associated With Atrial Fibrillation

Abstract: Background: The association of atrial fibrillation (AF) with cancer and cancer types is inconclusive. Similarly, data regarding the association of AF with different cancer therapies are controversial.Objectives: To study the association of AF with cancer subtypes and cancer therapies.Methods: We studied all patients aged 18–89 years who presented to the Feist Weiller Cancer Center, with or without a diagnosis of cancer, between January 2011 and February 2016. Electronic health records were systematically queri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 35 publications
3
12
0
Order By: Relevance
“…Together, these indicate that 15 Gy irradiation caused marked alterations in electrical conduction in our mouse model, consistent with that observed in large clinical cohort studies 14 .…”
Section: A/j Mice Develop Cardiac Toxicity Following Whole Heart Irra...supporting
confidence: 91%
“…Together, these indicate that 15 Gy irradiation caused marked alterations in electrical conduction in our mouse model, consistent with that observed in large clinical cohort studies 14 .…”
Section: A/j Mice Develop Cardiac Toxicity Following Whole Heart Irra...supporting
confidence: 91%
“…It is not uncommon for the practicing electrophysiologist to encounter large regions of abnormally reduced left atrial voltage (consistent with fibrotic scar) in the course of catheter ablation for AF in relatively young patients with a history of mantle irradiation for the treatment of Hodgkin lymphoma. Recently, a large retrospective single-center study of 14 600 patients concluded that a history of radiation therapy was an independent risk factor for developing AF . A separate, smaller case-control study found mediastinal irradiation to be an independent predictor of AF recurrence following catheter ablation in women with a history of breast cancer …”
supporting
confidence: 83%
“…Recently, a large retrospective single-center study of 14 600 patients concluded that a history of radiation therapy was an independent risk factor for developing AF. 6 A separate, smaller case-control study found mediastinal irradiation to be an independent predictor of AF recurrence following catheter ablation in women with a history of breast cancer. 7 The present study by Kim et al 2 extends and adds granularity to these findings.…”
mentioning
confidence: 95%
“…Those risk factors that were no longer significant were then dropped from the base model, thus arriving among those receiving radiation therapy (doses were not reported). 18 For a low to moderate range of radiation (not exceeding 4 Gy), we have examined radiation-associated risks of Brugada-type ECG, 19 early repolarization, 20 and complete right bundle branch block 21 among atomic bomb survivors, but found no evidence of altered risk.…”
Section: Discussionmentioning
confidence: 99%